Rethinking women empowerment at the crossroads of climate change and sustainable development - Mukoni, Manuku (International Journal of Development and Sustainability, 2016)
This paper is based on a gender analysis of literature on impacts of climate change. It uses feminist political ecology as a theoretical lens and the women empowerment framework as a tool of analysis. Paper reveals that inequitable distribution of rights, power and resources, and the repressive cultural gender roles and norms prohibit women’s full participation. Sustainable development can be realized if women empowerment is pivotal in developmental issues such as climate change. Women are not groomed to plan and make decisions concerning the interventions as these are imposed. They are brewed not to reflect on the strategies, thus failing to bring about women empowerment. Interventions used also focus on giving women increased access to practical gender needs such as education in the face of climate change. This paper argues that it is in addressing the strategic gender needs of women that empowerment can be realized. By focusing on practical gender needs of women, the strategies leave the structures of oppression and domination unchanged leading to their failure. The paper therefore calls for mitigation and adaptation strategies that ensure proactive empowerment of women. Potent empowerment strategies that focus on mobilization, conscientisation, participation and control must be invoked.